Vascular Inflammation in Systemic Autoimmunity - Cornelia Weyand (Frontiers Research Topics, 2017)
Plasticity and dynamism characterize the immune system as a tissue-integrating network with defensive functions. Blood and lymphatic vessel trees constitute the most evident and intuitive physical platform for the development of the net of interactions between immune cells, body tissues and foreign agents. Moreover vessel repair and immune patrolling are intimately linked physiological functions with common evolutionary roots. Not surprisingly variable degrees of vascular inflammation are often detectable in the setting of systemic inflammation and autoimmunity, whereas research in the field of cardiovascular pathology is progressively converging towards the identification of a common inflammatory background. The definition of the role of vascular inflammation in causing, sustaining and/or predicting the development of systemic autoimmunity constitute a challenging, unexplored frontier towards the development of a new generation of treatments and a better patient care.